About a snail, a toad and rodents: animal models for adaptation research - Eric W Roubos; Bruce G. Jenks; Lu eXu; Miyuki eKuribara; Wim J. J. M. Scheenen; Tamas eKozicz (Frontiers in Endocrinology, 2010)
Neural adaptation mechanisms have many similarities throughout the animal kingdom, enabling to study fundamentals of human adaptation in selected animal models with experimental approaches that are impossible to apply in man. This will be illustrated by reviewing research on three of such animal models, viz. (1) the egg-laying behavior of a snail, Lymnaea stagnalis: how one neuron type controls behavior, (2) adaptation to the ambient light condition by a toad, Xenopus laevis: how a neuroendocrine cell integrates complex external and neural inputs, and (3) stress, feeding and depression in rodents: how a neuronal network co-ordinates different but related complex behaviors. Special attention is being paid to the actions of neurochemical messengers, such as neuropeptide Y, urocortin 1 and brain-derived neurotrophic factor. While awaiting new technological developments to study the living human brain at the cellular and molecular levels, continuing progress in the insight in the functioning of human adaptation mechanisms may be expected from neuroendocrine research using invertebrate and vertebrate animal models.